La nutrición del paciente médico y quirúrgico grave - Ramirez V., Manuel A. (1973)
The present study shows the clinical and biochemical experience in eight medical and surgical patients during intravenous and gastrointestinal feeding. It is suggested that there is no difference between the surgical and medical patients when the are very ill, since both groups with oral and intravenous feeding may improve clinically and metabolically with thes techniques. Nitrogen losses would be massive in abcense of minimum amounts of essential nutrients.  It is concluded that there is a place for intravenous feeding in selected cases but preferably many patients should be handled by the gastrointestinal route, or if nedd be a combination of both.